2006
DOI: 10.1167/iovs.05-1305
|View full text |Cite
|
Sign up to set email alerts
|

Unique Distribution of Thrombospondin-1 in Human Ocular Surface Epithelium

Abstract: In the human ocular surface epithelium, basal cells of the CE and LE, but not of the CJE, synthesize TSP-1. High levels of TSP-1 are present only just below the CE. Its unique distribution may be related to corneal avascularity and integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 33 publications
1
46
0
Order By: Relevance
“…Additional Western blot analysis confirmed the expression of TSP-1 to be significantly higher in CCE than COE. 19 The same group indicated that TSP-1 also is the only antiangiogenic factor expressed solely by the corneal, but not conjunctival epithelia. 20 In our study, TSP-1 was not detected in normal conjunctiva and oral mucosa, but was detected beneath normal corneal epithelium, consistent with the findings of Sekiyama et al 20 and others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional Western blot analysis confirmed the expression of TSP-1 to be significantly higher in CCE than COE. 19 The same group indicated that TSP-1 also is the only antiangiogenic factor expressed solely by the corneal, but not conjunctival epithelia. 20 In our study, TSP-1 was not detected in normal conjunctiva and oral mucosa, but was detected beneath normal corneal epithelium, consistent with the findings of Sekiyama et al 20 and others.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Clinically, corneal NV following total LSCD is the most severe type, and the molecular mechanisms regulating NV formation and restoration of corneal avascularity after CLET have been reviewed extensively. 17,18 Recently, in vitro studies using cultivated oral and corneal epithelial cells from either humans [19][20] or rabbits 20,21 have shown that decreased expression of thrombospondin-1 (TSP-1) 20 and soluble fms-like tyrosine kinase-1 (sFlt-1), 22 and increased secretion of fibroblast growth factor-2 (FGF-2) 21 may be responsible for the enhanced angiogenic potential after COMET. Until now, clinicopathologic studies focusing on angiogenesis-related factors in patients receiving COMET have been lacking.…”
mentioning
confidence: 99%
“…Moreover, the long variant form of type XII collagen has been identified in the corneal epithelial BM zone, Bowman's layer, and in the interfibrillar matrix of the corneal stroma, but was absent in the limbal and conjunctival epithelial BM zones (Wessel et al, 1997). Further differences in distribution along the ocular surface epithelia have been documented for tenascin-C, collagen types VIII, XII and XIV, fibrillin-1, and thrombospondin-1 (Ljubimov et al, 1996(Ljubimov et al, , 1998bSekiyama et al, 2006). Differences in patterns of basal adhesion structures between the corneal and limbal epithelia have also been reported, such as a smaller number of hemidesmosomes, a discontinuous BM, a complex network of anchoring fibrils, and a more irregular basal cell surface in the limbal area (Gipson, 1989).…”
Section: Extracellular Matrix and Stem Cell Compartmentsmentioning
confidence: 98%
“…7 Moreover, TSP-1-deficient mice spontaneously develop conjunctival inflammation with age. 22 Regarding TSP-1 expression in human conjunctiva, some studies reported a mild and focal TSP-1 staining in normal human conjunctival epithelium, 23 while others reported detection of the protein in corneal, but not in conjunctival epithelia, 24,25 suggesting a pivotal role of TSP-1 in preventing corneal angiogenesis. A reported correlation between a polymorphism in the TSP-1 gene (THBS-1) and chronic ocular surface inflammation in humans further supports the importance of TSP-1 in immunomodulation.…”
Section: Introductionmentioning
confidence: 99%